Effect of endovascular reperfusion in relation to site of arterial occlusion. (23rd February 2016) - Lemmens, Robin; Hamilton, Scott A.; Liebeskind, David S.; Tomsick, Tom A.; Demchuk, Andrew M.; Nogueira, Raul G.; Marks, Michael P.; Jahan, Reza; Gralla, Jan; Yoo, Albert J.; Yeatts, Sharon D.; Palesch, Yuko Y.; et al.
Abstract : Objective: To assess whether the association between reperfusion and improved clinical outcomes after stroke differs depending on the site of the arterial occlusive lesion (AOL). Methods: We pooled data from Solitaire With the Intention for Thrombectomy (SWIFT), Solitaire FR Thrombectomy for Acute Revascularisation (STAR), Diffusion and Perfusion Imaging Evaluation for Understanding Stroke Evolution Study 2 (DEFUSE 2), and Interventional Management of Stroke Trial (IMS III) to compare the strength of the associations between reperfusion and clinical outcomes in patients with internal carotid artery (ICA), proximal middle cerebral artery (MCA) (M1), and distal MCA (M2/3/4) occlusions. Results: Among 710 included patients, the site of the AOL was the ICA in 161, the proximal MCA in 389, and the distal MCA in 160 patients (M2 = 131, M3 = 23, and M4 = 6). Reperfusion was associated with an increase in the rate of good functional outcome (modified Rankin Scale [mRS] score 0–2) in patients with ICA (odds ratio [OR] 3.5, 95% confidence interval [CI] 1.7–7.2) and proximal MCA occlusions (OR 6.2, 95% CI 3.8–10.2), but not in patients with distal MCA occlusions (OR 1.4, 95% CI 0.8–2.6). Among patients with M2 occlusions, a subset of the distal MCA cohort, reperfusion was associated with excellent functional outcome (mRS 0–1; OR 2.2, 95% CI 1.0–4.7). Conclusions: The association between endovascular reperfusion and better clinical outcomes is more profound in patients with ICA and proximal MCA occlusions compared to patients with distal MCA occlusions. Because there are limited data from randomized controlled trials on the effect of endovascular therapy in patients with distal MCA occlusions, these results underscore the need for inclusion of this subgroup in future endovascular therapy trials.